Utility of Anti-DSF70 antibodies to predict connective tissue disease in patients originally presenting with idiopathic interstitial pneumonia - Lyu, Yan; Kreuter, Michael (Respiration, 2019)
Background: Anti-DFS70 antibodies, corresponding to the dense fine speckled antinuclear antibody (ANA) pattern in HEp-2 substrates, have been observed in chronic inflammatory conditions, cancer and in healthy individuals but in only a small percentage of patients with connective tissue diseases (CTD). Objectives: The study was aimed to investigate the possible role of Anti-DFS70 antibodies to distinguish CTD associated interstitial lung disease (CTD-ILD) from idiopathic interstitial pneumonia (IIP) and to explore potential correlations between anti-DFS70 antibodies and clinical parameters. Methods: Serum samples were collected from 49 healthy controls (HC), 35 scleroderma-ILD (SSc-ILD) patients as negative controls for anti-DFS70 antibody, and 260 patients with the initial diagnosis IIP including 100 nonspecific interstitial pneumonia (NSIP) and 160 idiopathic pulmonary fibrosis (IPF) patients. ANA pattern was identified by indirect immunofluorescence on HEp-2 cells and anti-DFS70 antibodies were measured in serum by ELISA. Results: Serum anti-DFS70 antibodies were less frequently seen in ILD and SSc-ILD patients compared to HCs. Thirty-seven patients (34 initial idiopathic NSIP and 3 initial IPF patients) developed CTD during 24 months of follow-up, most of them combined with ANA positivity and anti-DFS70 antibody negativity. Anti-DFS70 antibody positivity was not significantly different between CTD-ILD and idiopathic ILD. Conclusions: The frequency of serum anti-DFS70 antibody is markedly decreased in patients with ILDs. Anti-DFS70 antibodies may be useful to predict CTD development in ILD patients.
Gesehen am 13.09.2019